Studi Efektifitas Dan Kinerja Instalasi Pengolahan Air Limbah (Ipal) Pada Peternakan Sapi Skala Rumah Tangga - Yunita Kusuma Bintang; Dian Chandrasasi; Riyanto Haribowo (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
Argosari Village is one of the villages that has cattle farms in Malang Regency. This research was conducted in one of the houses in Argosari Village and has 6 (six) of cows. In one day, each cow produces 100-150 liters of liquid waste. However, the liquid waste is immediately discharged into the drainage channel because there is no effort to process wastewater. On the results of laboratory tests, samples of wastewater, BOD, COD, TSS, NH3-N and pH in wastewater were respectively 4488 mg/L, 11000 mg/L, 850,5 mg/L, 479,3 mg/L, 8,5 mg/L. Based on the Regulation of the Minister of Environment Number 11 of 2009, the liquid waste has not met the quality standard. Wastewater Treatment Plant (WWTP) is needed to save reserves on cattle wastewater. The suitable installation in this condition is an initial settling basin, aerobic biofilter basin and a final settling basin. Aerobic biofilter is used so that liquid waste can be used biologically by using the media of honeycomb biofilter to grow and breed microorganisms. After processing the WWTP, there is a decrease in effluent, so WWTP can produce effluent BOD of 80,78 mg/L, COD = 198 mg/L, TSS = 5,10 mg/L, NH3-N = 23,9 mg/L and pH = 8,5.